Endocannabinoids inhibit neurogenic inflammation in murine joints by a non-canonical cannabinoid receptor mechanism. (August 2017) - Krustev, Eugene; Muley, Milind M.; McDougall, Jason J.
Abstract: Neurogenic inflammation is a local inflammatory response that is driven by the peripheral release of neuropeptides from small diameter afferents which occurs in many organs including joints. The knee joint has a rich endocannabinoid system which has been shown to decrease acute synovitis. The aim of this study was to investigate the influence of joint afferents on leukocyte-endothelial interactions within the synovial microcirculation of mice and determine the role of endocannabinoids on this inflammatory response. Electrical, antidromic stimulation of the saphenous nerve decreased leukocyte rolling at the lowest frequency tested (0.5 Hz), while increasing leukocyte rolling at higher frequencies (2.0 and 5.0 Hz). The leukocyte rolling effect of nerve stimulation was completely abolished by pre-treating the knee with the vasoactive intestinal peptide antagonist VIP6–28 ; however, neither calcitonin gene related peptide nor substance P antagonism had an effect on this neurogenic inflammatory response. Treating knees with the endocannabinoid breakdown inhibitor URB597 completely blocked leukocyte rolling and this effect could be reversed with the non-canonical cannabinoid antagonist O-1918. These results provide evidence that antidromic stimulation of the mouse saphenous nerve promotes leukocyte rolling within the synovial microcirculation, and that endocannabinoids can attenuate this neurogenic inflammatory response. Highlights: Antidromic stimulation of joint nerves altered leukocyte trafficking in the articular circulation. Low frequency nerve stimulation inhibited leukocyte rolling while higher frequencies were found to be pro-inflammatory. This neurogenic inflammatory response was found to be VPAC receptor-dependent. Blocking endocannabinoid hydrolysis in the joint reduced neurogenic inflammation via a non-canonical cannabinoid receptor.